2013
DOI: 10.1038/eye.2013.123
|View full text |Cite
|
Sign up to set email alerts
|

Association study of genetic variants on chromosome 7q31 with susceptibility to normal tension glaucoma in a Japanese population

Abstract: The caveolin 1 to caveolin 2 (CAV1-CAV2) gene region on chromosome 7q31 has been reported to be associated with susceptibility to primary open angle glaucoma (POAG) and normal tension glaucoma (NTG) in previous studies. We investigated whether genetic variants in the CAV1-CAV2 region are associated with NTG in Japanese patients. Two hundred and ninety-two Japanese patients with NTG and 352 Japanese healthy controls were recruited. We genotyped three singlenucleotide polymorphisms; that is, rs1052990, rs4236601… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
20
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 13 publications
5
20
1
Order By: Relevance
“…55 In addition, both miR-224-5p and CAV2 are expressed in the eye. 56,57 These data may suggest an allele-specific regulation of CAV2 by miR-224-5p as a functional mechanism underlying the observed GWAS association.…”
Section: Discussionmentioning
confidence: 69%
“…55 In addition, both miR-224-5p and CAV2 are expressed in the eye. 56,57 These data may suggest an allele-specific regulation of CAV2 by miR-224-5p as a functional mechanism underlying the observed GWAS association.…”
Section: Discussionmentioning
confidence: 69%
“…We also genotyped the SNP rs1052990 in the Osaka cohort for comparison with a previous study in Japanese12 as detailed in the methods. SNP rs4236601 was associated with POAG in the Shantou cohort prior to (P = 0.0079, OR = 4.23) and after adjusting for age and gender (P = 0.0037, OR = 6.09).…”
Section: Resultsmentioning
confidence: 99%
“…Further studies investigated the link between this polymorphism and POAG with divergent results: some studies confirmed the original conclusion, whereas others did not find a connection between this polymorphism and POAG. [3][4][5][6] Although the findings are not consistent, CAV1 has been implicated in the pathology of glaucoma.…”
mentioning
confidence: 99%